Serving the chain? De Nederlandsche Bank and the last decades of slavery, 1814-1863 - Fatah-Black, Karwan (Leiden University Press, 2023)
'Serving the chain?' is a history of De Nederlandsche Bank in which particular attention is paid to its links with slavery, both as a factor in the economy and as a subject of political debate.